Estimation of anisotropy parameters using the P-wave velocities on a cylindrical shale sample - Nadri, D.; Sarout, J.; Bona, Andrej; Dewhurst, D. (SEG, 2011)
In this paper we present a new approach to the estimation of the Thomsen anisotropy parameters and symmetry axis coordinates from the P-wave traveltime measurements on cylindrical shale samples. Using the tomography-style array of transducers, we measure the ultrasonic P-wave ray velocities to estimate the Thomsen anisotropy parameters for a transversely isotropic shale sample. This approach can be used for core samples cut in any direction with regard to the bedding plane, since we make no assumption about the symmetry axis directions and will estimate it simultaneously with the anisotropy parameters. We use the very fast simulated re-annealing to search for the best possible estimate of the model parameters. The methodology was applied to a synthetic model and an anisotropic shale sample.